Using the Strategic Energetic Resources or Electrical Energy as a Possible Pressure Tool - Daniel Nicolae Fita; Mila Ilieva Obretenova; Sorina Daniela Stanila; Adriana Zamora; Safta Gheorghe Eugen; Florin Grecu-Muresan (Advances and Challenges in Science and Technology Vol. 3, 2023)
Electrical energy is the energy derived from electric potential energy or kinetic energy of the charged particles. In general, it is referred to as the energy that has been converted from electric potential energy. We can define electrical energy as the energy generated by the movement of electrons from one point to another. The movement of charged particles along/through a medium (say wire) constitute current or electricity. The world’s major energy powers desire to own and control the entire chain of global energy in order to use primary energetic resources or electricity as a possible energetic tool or pressure tool in the context of blackmail and profitabilty due to the increasing frequency of cases of energetic collapse around the world manifested by the lack of finite primary energetic resources (oil, gas, coal, and uranium) or electricity to the final consumers. By the lack of supplying the primary energy or electricity to final consumers leads to the crises that cause societal disproportions causing extreme damage to the safety of citizens, industry, the national economy and thus national security, because all areas of a state economy depend on primary energetic resources or electricity. In this context, the energy security of a state becomes an important pillar of national, regional and international security, bringing safety, stability and well-being to the final consumers for electricity usage.